2020
DOI: 10.2147/cmar.s222572
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Hereditable Mutation of MSH2 Gene Associated with Lynch Syndrome in a Five Generation Chinese Family</p>

Abstract: In order to clarify which variants of the MMR gene could provide current "healthy" members in affected families a more accurate risk assessment or predictive testing. Patients and Methods: One family, which meets the criteria according to both Amsterdam I/II and Bethesda guidelines, is reported in this study. The proband and some relatives of the patient have been investigated for whole genome sequencing, microsatellite instability, immunohistochemical MMR protein staining and verified by Sanger sequencing. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Genomic DNA was isolated from blood samples of III-14 and III-15 and tested for MSI. A five-marker panel including two mononucleotide repeats (BAT25 and BAT26) and three dinucleotide repeats (D2S123, D5S346, and D17S250), which is recommended by the National Cancer Institute (NCI) Workshop on MSI for Cancer Detection and Familial Predisposition, was used as previously described ( 25 ). Oligonucleotide primers were fluorescently labeled, and PCR products were evaluated using the 3500DX Genetic Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from blood samples of III-14 and III-15 and tested for MSI. A five-marker panel including two mononucleotide repeats (BAT25 and BAT26) and three dinucleotide repeats (D2S123, D5S346, and D17S250), which is recommended by the National Cancer Institute (NCI) Workshop on MSI for Cancer Detection and Familial Predisposition, was used as previously described ( 25 ). Oligonucleotide primers were fluorescently labeled, and PCR products were evaluated using the 3500DX Genetic Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Several polymorphism studies have shown the strong association of SNPs toward the susceptibility of cancer. 9,10 Elek et al 11 have recently demonstrated that SNP rs34944508 influences MGAT5 expression, which catalyzes the addition of Nacetylglucosamine (GlcNAc) in β [1][2][3][4][5][6] linkage to mannose of N-linked oligosaccharide, which is a characteristic of invasive lung malignancies. A study conducted by Slovakova et al 12 on promoter polymorphisms for selected MMR genes viz MSH2 (rs2303425) has evaluated the risk of cancer development in both dominant and recessive genetic models and demonstrated that polymorphism of MMR genes MSH2 is associated with a risk of developing sporadic cancer and hereditary tumors in Slovak people.…”
Section: F I G U R E 1 Location Of Different Domains On Msh2 Proteinmentioning
confidence: 99%
“…MutS Homolog 2 (MSH2) protein plays an essential role in DNA repair and is associated with different cancer such as hereditary nonpolyposis colorectal cancer (HNPCC), Lynch syndrome, and lung cancer 1–3 . MSH2 comprises two interaction domains (MSH3/MSH6 and MSH2/PMS2) and one DNA binding domain, which are present in two different locations on the gene (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynch syndrome (LS) is an autosomal dominant syndrome linked to a variety of cancers of the colon, endometrium, ovary, and others ( 1 , 2 ). LS is mainly caused by germline and epistatic mutations in the human mismatch repair (MMR) gene ( 3 ).…”
Section: Introductionmentioning
confidence: 99%